Individual differences in change blindness are predicted by the strength and stability of visual representations. Issue 1 (24th January 2019) - Andermane, Nora; Bosten, Jenny M; Seth, Anil K; Ward, Jamie
Abstract: The phenomenon of change blindness reveals that people are surprisingly poor at detecting unexpected visual changes; however, research on individual differences in detection ability is scarce. Predictive processing accounts of visual perception suggest that better change detection may be linked to assigning greater weight to prediction error signals, as indexed by an increased alternation rate in perceptual rivalry or greater sensitivity to low-level visual signals. Alternatively, superior detection ability may be associated with robust visual predictions against which sensory changes can be more effectively registered, suggesting an association with high-level mechanisms of visual short-term memory (VSTM) and attention. We administered a battery of 10 measures to explore these predictions and to determine, for the first time, the test–retest reliability of commonly used change detection measures. Change detection performance was stable over time and generalized from displays of static scenes to video clips. An exploratory factor analysis revealed two factors explaining performance across the battery, that we identify as visual stability (loading on change detection, attention measures, VSTM and perceptual rivalry) and visual ability (loading on iconic memory, temporal order judgments and contrast sensitivity). These results highlight the importance of strong, stable representations and the ability to resist distraction, in order to successfully incorporate unexpected changes into the contents of visual awareness.